Can nanoparticles be useful for antiviral therapy? - Lozovski, V.; Lysenko, V.; Pyatnitsia, V.; Spivak, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
In this paper, optical properties of the system consisting of mesoparticles
(small dielectric particles) and nanoparticles (quantum dots) of various shapes have been
considered. This system can be characterized by resonant absorption of electromagnetic
waves and used for developing the new approach to antiviral therapy.